The Glasgow Beneﬁt Inventory: a systematic review of the use and value of an otorhinolaryngological generic patient-recorded outcome measure - Hendry, J.; Chin, A.; Swan, Iain R.C.; Akeroyd, Michael A.; Browning, George G. (Wiley, 2016)
The Glasgow Benefit Inventory (GBI) is a validated, generic patient-recorded outcome measure widely used in otolaryngology to report change in quality of life post-intervention.To date, no systematic review has made (i) a quality assessment of reporting of Glasgow Benefit Inventory outcomes; (ii) a comparison between Glasgow Benefit Inventory outcomes for different interventions and objectives; (iii) an evaluation of subscales in describing the area of benefit; (iv) commented on its value in clinical practice and research.Systematic review.'Glasgow Benefit Inventory' and 'GBI' were used as keywords to search for published, unpublished and ongoing trials in PubMed, EMBASE, CINAHL and Google in addition to an ISI citation search for the original validating Glasgow Benefit Inventory paper between 1996 and January 2015.Papers were assessed for study type and quality graded by a predesigned scale, by two authors independently. Papers with sufficient quality Glasgow Benefit Inventory data were identified for statistical comparisons. Papers with <50% follow-up were excluded.A total of 118 eligible papers were identified for inclusion. A national audit paper (n = 4325) showed that the Glasgow Benefit Inventory gave a range of scores across the specialty, being greater for surgical intervention than medical intervention or 'reassurance'. Fourteen papers compared one form of surgery versus another form of surgery. In all but one study, there was no difference between the Glasgow Benefit Inventory scores (or of any other outcome). The most likely reason was lack of power. Two papers took an epidemiological approach and used the Glasgow Benefit Inventory scores to predict benefit. One was for tonsillectomy where duration of sore throat episodes and days with fever were identified on multivariate analysis to predict benefit albeit the precision was low. However, the traditional factor of number of episodes of sore throat was not predictive. The other was surgery for chronic rhinosinusitis where those with polyps on univariate analysis had greater benefit than those without. Forty-three papers had a response rate of >50% and gave sufficient Glasgow Benefit Inventory total and subscales for meta-analysis. For five of the 11 operation categories (vestibular schwannoma, tonsillectomy, cochlear implant, middle ear implant and stapes surgery) that were most likely to have a single clear clinical objective, score data had low-to-moderate heterogeneity. The value in the Glasgow Benefit Inventory having both positive and negative scores was shown by an overall negative score for the management of vestibular schwannoma. The other six operations gave considerable heterogeneity with rhinoplasty and septoplasty giving the greatest percentages (98% and 99%) most likely because of the considerable variations in patient selection. The data from these operations should not be used for comparative purposes. Five papers also reported the number of patients that had no or negative benefit, a potentially a more clinically useful outcome to report. Glasgow Benefit Inventory subscores for tonsillectomy were significantly different from ear surgery suggesting different areas of benefitThe Glasgow Benefit Inventory has been shown to differentiate the benefit between surgical and medical otolaryngology interventions as well as 'reassurance'. Reporting benefit as percentages with negative, no and positive benefit would enable better comparisons between different interventions with varying objectives and pathology. This could also allow easier evaluation of factors that predict benefit. Meta-analysis data are now available for comparison purposes for vestibular schwannoma, tonsillectomy, cochlear implant, middle ear implant and stapes surgery. Fuller report of the Glasgow Benefit Inventory outcomes for non-surgical otolaryngology interventions is encouraged.